Chemoablation of prostate in dogs - Canpolat, I; Eroksuz, Y (Indian Veterinary Journal, 2005)
[Abstract Not Available]
Keywords: Absolute Ethanol; Injection Treatment; Ablation; Guidance; Therapy; Tumors